Calcium alginate gel capsules loaded with inhibitor for corrosion protection of downhole tube in oilfields. (January 2015) - Wang, Lida; Zhang, Cheng; Xie, Hongbin; Sun, Wen; Chen, Xiuling; Wang, Xuankui; Yang, Zhengqing; Liu, Guichang
Highlights: Calcium alginate gel capsules loaded with inhibitor were prepared by piercing-solidifying method. Introduced heavy additive accelerates the sinking of capsules loaded with inhibitor. Capsules gradually release inhibitor during its sinking to the bottom of oilwell. Tubes from top to bottom in oilwell were effectively protected by inhibitor. Abstract: Calcium alginate gel (Alg-Ca 2+ ) capsules loaded with inhibitor and heavy additive were prepared by a piercing-solidifying method. The releasing process of inhibitor together with their inhibitive effect on P110 steel in CO2 -saturated 3.5 wt.% NaCl aqueous solution was investigated by ultraviolet–visible spectrophotometer, scanning electron microscopy, electrochemical impedance spectroscopy. Our experiments revealed that the synthesized capsules can gradually release inhibitors during their sinking process, and effectively prevent the tube in oilwell from corrosion. Introducing appropriate amount of heavy additive BaSO4 into the inhibitor-loaded capsules facilitates their sinking processes and corrosion protection performance.